“Você deu sorte !”: um estudo sobre as absolvições do crime de tráfico de drogas na Comarca do Recife. - Ramos, Laís Alves Xavier (2024)
This research aims to understand the reasons that led to the acquittal of 44 defendants for drug trafficking in the District of Recife, as part of the research agenda on judicial behavior. Starting from the assumption that the criminal process is a reconstruction of the facts by the actors of the Justice System, a multiple case study, with mixed methods, was carried out, based on the quantitative characterization of the cases in question – characteristics of the defendants and the process itself – and, subsequently, the qualitative analysis of 35 sentences from cases filed between 2021 and 2023 in the criminal courts of the District of Recife with the help of a tool based on grounded theory, known as data-based theorization (TFD). Four categories of acquittal were extracted from the data, namely 1) motivated by illegal access to the defendant's domicile; 2) due to doubt about the location of the drug; 3) by invalidating the police narrative; and 4) by applying the principle of in dubio pro reo. It was argued that the magistrate's own sense is a central motivation for acquittal sentences, which is evidenced more or less clearly in his text, depending on the case. The research is part of the human rights studies of the PPGD/Unicap research line and contributes to the understanding of the scenario of punitiveness peculiar to the Brazilian reality.